Design and Development of the Andalas University Transportation Center (PUSTRANS) Website Using Laravel Framework - Novi Yona Sidratul Munti; Muhammad Faridz Maulana (Indonesian Journal of Innovation Science and Knowledge, 2026)
The rapid development of information technology requires institutions to shift from manual data management to integrated digital systems. The Center for Transportation of Universitas Andalas (PUSTRANS) previously faced challenges such as delayed information delivery, difficulty in data retrieval, and inefficient content management. This study aims to design and develop the official PUSTRANS website as a digital information medium as well as a content management system (CMS) with an admin panel. The method used is the Agile approach, covering needs analysis, system design (use case diagram, ERD, and flowchart), implementation, and testing. The system was developed using the Laravel framework (MVC architecture), PHP programming language, MySQL database, and frontend technologies including HTML, CSS, and JavaScript. The development results produced a website with two types of users: administrators who can perform CRUD operations on news, articles, activity agendas, webinars, and categories through a dashboard, and visitors who can access information dynamically without logging in. The system successfully displays content in real-time, improves data management efficiency, and supports the digitalization of information within PUSTRANS. The website has proven to be user-friendly, centralized, and accessible anytime. Further development is recommended to include interactive user features, UI/UX improvements, and integration with other systems. Keywords : website, Laravel, CMS, PUSTRANS, information system, transportation